Violence, image and victim in Bataille, Agamben and Girard - Lechte, John (2023)
What is violence – what is an image? How does violence relate to the image, and how do violence and the image implicate and define the victim? Explores the link between violence and the image for the first timeClarifies the role of violence and the image in the work of Georges Bataille, Giorgio Agamben and René GirardShows the implications of Christ being equated with the imageProvides new insights into what violence is and what the image is, which makes this a book for out timeBataille, Agamben and Girard are thinkers of the moment in as much as they each aim to explain the basis of society and culture in the context of power and the sacred. To study power and the sacred, the book shows, is to reveal the connection between violence and the image, a connection that shows what it means to be a victim. Separate chapters are devoted to the study of violence and the image as these appear in the work of Bataille, Agamben and Girard.The book concludes that no study of violence and the image can avoid engaging with the issue of the injustice of being a victim